Rapid, conservative, multidisciplinary miniscrew-assisted approach for treatment of mandibular fractures following plane crash - Azita Tehranchi; Hossein Behnia; Farnaz Younessian; Mostafa Sadeghi Ghochani (Wolters Kluwer Medknow Publications, 2013)
Mandibular fractures are among the most common facial injuries. This case report demonstrates the efficacy of simultaneous usage of miniscrews and direct bonding techniques without open reduction in an extensive traumatized patient. A 25-year-old girl with multiple injuries in the head and facial region 1 month after a plane crash accident was referred to manage the mandibular fractures. Due to the presence of multiple injuries, a conservative treatment of symphysiseal fracture was performed. In order to keep the fractured fragments of the mandible close together, the anterior teeth of the lower arch were tied by means of the orthodontic wire. Ten miniscrews were used to improve the anchorage units and also, settling the occlusion by means of light intermaxillary elastics. Following the active treatment, clinical and radiographic analysis showed satisfactory healing without any periodontal involvement of the teeth in the fracture line.